Doctrinal background and legal basis of US military presence in Europe mid 1940’s – early 1950’s - Viacheslav Masniy (Американська історія і політика, 2016)
The article deals with the formation and development of concepts and doctrines of foreign policy of the United States, documents and agreements that formed the basis of the creation and replacement of contingents of the Armed Forces of the United States in Europe after World War II. The article analyses the basic milestones in the development and approval of these doctrines, especially the key texts and documents of the concept of containment – “Long Telegram” of February 22, 1946, which was sent to the State Department by counselor of the US Embassy in Moscow J. F. Kennan, his article «Sources of Soviet Conduct», published in «The Foreign Affairs» in July 1947 under the pseudonym «X», and the Truman Doctrine, formulated in the speech of the President of the USA Harry Truman at the joint session of the Senate and House of Representatives on March 12, 1947, the role and place of international and American legal documents and agreements on military cooperation between the US and European countries in international relations in Europe. The features of the Cold War origins influence on development of American vision of cooperation with European countries are described. The history of the formation, location and operation of US occupation troops in German is considered, the process of their transformation into the US European Command troops is also described. Attention is focused on the conceptual and theoretical aspects of the described processes and events.